Improving the Color Stability of Naturally Colored Silk by Cross-Linking the Sericin with Phytic Acid - Mingbo Ma; Pirah Ayaz; Wanhui Jin; Wenlong Zhou (International Journal of Polymer Science)
The color of naturally colored silk (NCS) fades easily during home washing due to the loss of pigment accompanied by dissolution of the sericin. In this study, phytic acid was used to cross-link the sericin of NCS and reduce its solubility, aiming at improving the color fastness of NCS to repeated washing. It was found that the sericin-fixing effect increased as the concentration of phytic acid to 1.0 wt% and the cross-linking time to 5 h increased and then reached a constant level. Cross-linking at pH 7.0-8.5 and temperature 30-40°C could obtain relatively good sericin-fixing effects. The cross-linked NCS showed low sericin loss during the degumming and had much better color fastness to repeated washing as compared with the samples before cross-linking. The cross-linking method proposed in this study may be not only a kind of solution for improving the color fastness of NCS with high practicality but also an alternative for cross-linking sericin-based materials in the biomedical field.